ANALISIS KESULITAN SISWA PADA PEMBAHASAN MATERI PENGOLAAN DATA KELAS VI SDN PONDOK JAGUNG TIMUR - Unaenah, Een; Yuliawati, Dea; Aen, Kurotul; Sahrurosi, Putri Adinda (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study seeks to investigate the challenges that students encounter while discussing data management concepts in their sixth-grade curriculum. Data management is a substantial component of their mathematics lessons, where they delve into collecting, organizing, and assessing data. However, within this learning journey, certain students may encounter difficulties in comprehending and applying data management concepts effectively. Our study is geared towards understanding the specific hurdles faced by Class VI students when engaging with data management topics. The research methodology entails data collection through classroom observations, student interviews, and the analysis of student practice questions. The findings of the study highlight that several students encounter challenges across various aspects of comprehending data management material.